Cydninae (Hemiptera, Heteroptera, Cydnidae) in Brazil: updated checklist, new records, and description of Tominotus ondulatus sp. nov. - Avendaño, José Mauricio; Grazia, Jocelia; Schwertner, Cristiano Feldens (Zootaxa, 2017)
Cydninae is the largest subfamily among burrower bugs all around the world and for Brazil the genera Cyrtomenus, Dallasiellus, Ectinopus, Melanaethus, Onalips, Pangaeus, Prolobodes and Tominotus were reported with a total of 39 species, so far. Basing on the material of nine entomological collections, we updated the list to 47 species including new records and a new species, Tominotus ondulatus sp. nov. described from Restinga, Rio Grande do Sul. Distribution maps and photos of dorsal habits for several species are also provided.